The role of coastal women in the development of marine tourism in Madello Village - Dewi, Surya (Technium Social Sciences Journal, 2021)
This study aims to see the extent of the role of women in the development of marine tourism in Madello village, Barru district. This study uses a descriptive method with a qualitative approach, while data collection is done by means of observation, interviews and documentation. Based on research in the field, it was found that the role of coastal women in Madello village was engaged in the service economy sector in the manufacture of mangrove syrup, processed seaweed, shrimp paste and fish shredded processing spread across Ujunge hamlet and Pannikiang island. Efforts to optimize women's empowerment and efforts to awaken poor areas can be pursued, one of which can be done by assisting women to increase existing women's potential, through developing productive businesses and diversifying local products in groups.